2016
DOI: 10.1128/jvi.02159-15
|View full text |Cite
|
Sign up to set email alerts
|

γδ T Cells Play a Protective Role in Chikungunya Virus-Induced Disease

Abstract: Chikungunya virus (CHIKV) is an alphavirus responsible for causing epidemic outbreaks of polyarthralgia in humans. Because CHIKV is initially introduced via the skin, where ␥␦ T cells are prevalent, we evaluated the response of these cells to CHIKV infection. CHIKV infection led to a significant increase in ␥␦ T cells in the infected foot and draining lymph node that was associated with the production of proinflammatory cytokines and chemokines in C57BL/6J mice. ␥␦ T cell ؊/؊ mice demonstrated exacerbated CHIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 100 publications
1
23
0
1
Order By: Relevance
“…After nine months of experimental study, our present study shows that a naturally existing oncolytic virus, alphavirus M1, did not cause significant harm to the health of cynomolgus macaques after three rounds of repeated intravenous injections (totally including 18 doses,each dose up to 1×10 9 pfu), except for the temporarily increased monocyte in the peripheral blood of the experimental group after M1 virus injection, The increment of monocyte in peripheral blood of cynomolgus macaques had been reported in western equine encephalitis virus study by other researchers 17 . In fact, it was also reported that alphavirus can infect monocyte and spread in human body via monocyte 18,19 . Although recruitment of CCR2(+) monocytes can contribute to inflammation 20 , monocytes also appears to be critical for preventing excessive pathology and resolving inflammation following alphavirus infection 21 .…”
Section: Discussionmentioning
confidence: 98%
“…After nine months of experimental study, our present study shows that a naturally existing oncolytic virus, alphavirus M1, did not cause significant harm to the health of cynomolgus macaques after three rounds of repeated intravenous injections (totally including 18 doses,each dose up to 1×10 9 pfu), except for the temporarily increased monocyte in the peripheral blood of the experimental group after M1 virus injection, The increment of monocyte in peripheral blood of cynomolgus macaques had been reported in western equine encephalitis virus study by other researchers 17 . In fact, it was also reported that alphavirus can infect monocyte and spread in human body via monocyte 18,19 . Although recruitment of CCR2(+) monocytes can contribute to inflammation 20 , monocytes also appears to be critical for preventing excessive pathology and resolving inflammation following alphavirus infection 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Gamma-delta T cells are reported to play a protective role against CHIKV infection (59). These cells do not affect CHIKV virus replication in the joints.…”
Section: Gamma-delta (γδ) T Cellsmentioning
confidence: 99%
“…Instead, their absence is associated with increased joint swelling and tissue damage in the infected mice. The absence of γδ T cells were also linked to increased monocyte infiltration to the joints and increased levels of pro-inflammatory mediators CCL2, CXCL9, and IFN-γ (59). Hence, the resulting pro-inflammatory milleu leads to more inflammatory cell infiltration and result in tissue damage that is observed during CHIKV infection.…”
Section: Gamma-delta (γδ) T Cellsmentioning
confidence: 99%
“…γδ T cells have been shown to respond to and participate in host defense responses in a variety of infectious diseases, including viral, bacterial, and parasite-induced disease, many at the mucosal surface [2,91]. Recently, γδ T cells have been found to be important for protection against emerging viruses such as Chikungunya and West Nile virus [92,93]. In HIV infection, the peripheral subset of human γδ T (Vδ2) cells is severely depleted and does not completely recover, even in patients who have had successful antiretroviral treatment.…”
Section: Role Of γδ T Cells In Infectious Diseasesmentioning
confidence: 99%